Mallomonas alpestrina sp. nov. (Synurales, Chrysophyceae, Stramenopiles) and its spineless relatives—Mallomonas alata group - Nemcova, Yvonne; Pichrtova, Martina; Zeisek, Vojtech (Phytotaxa, 2015)
In this paper, we define the Mallomonas alata group and describe M. alpestrina sp. nov. from an oligotrophic high mountain glacial lake on the slopes of Haba Xue Shan (Haba Snow Mountain), China. The Mallomonas alata group is excluded from the M. pumilio group primarily based on the approximately triangular shape of the collar scales, the small hook-like protruded dome, and one considerably broader anterior flange of the body scale. We extend previous research on small species from the section Torquatae with reticulated scale-shield pattern. Molecular genetic data for the Mallomonas alata group species are not currently available; therefore, we provide detailed information on scale and scale-case morphology, environmental requirements, and geographical distribution of these species.